Efisiensi Daya Pada Smartlock Bike-Sharing Berbasis LoRaWAN Dengan Metode GPS Duty Cycle - Alfian Andi Nugroho; Ahmad Ashari (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
Bike-sharing or commonly called Public-Use Bycycle (PUB), Bycycle Transit, or Smartbike is a short-term bicycle rental system that allows users to borrow bikes from a self-serve bike-sharing station to a point. Due to technological advances, the bike-sharing system that was once simple, now also utilizes technology in its operations. The modern bike-sharing system is equipped with IoT and GPS technology that is useful for sending data on the actual location of the bicycle, bicycle lock conditions, or even for M2M communication with other stations or bikes. However, this data transmission can cause the battery to run out quickly because of frequent sending and using GSM which requires a large enough power that is 200 mA when sending data and 80 mA when receiving, so that an alternative solution is needed to be able to save power. Therefore, the GPS Duty cycle is used as a method to increase power efficiency on the smartlock. In addition to using the GPS Duty cycle, this study also uses LoRa as a data delivery medium which has lower power usage compared to GSM technology. The results of this study are the duty-cycle algorithm can increase the efficiency of power usage up to 59% when compared to smartlocks that do not use the duty-cycle algorithm. It was also found that LoRa succeeded in sending data up to a distance of 750 meters with a successful delivery of 39.3 percent